Analisis Pengaruh Penggunaan Serat Polypropylene Terhadap Self Compacting Concrete (SCC) dengan Bahan Dasar Agregat Kasar Gradasi Senjang (Gap-Grading) - Ulini'am, Adipati Syahidullah; Noorhidana, Vera Agustriana; Irianti, Laksmi; Isneini, Mohd (Universitas Lampung, 2021)
In general, Self Compacting Concrete (SCC) uses coarse aggreggate with dense graded for mix composition. However, in certain places, sometimes the sources of aggreggate are limited and there’s no stone crusher with possibly use coarse aggreggate with gap graded. H. This research was conducted for investigate the effect of polypropylene fiber additions to SCC with gap graded on workability, compressive strength, splitting tensile strength, and bending strength. Test result for Slump-Flow and T50 for both of gradation with Vf 0%, 0,05%, and 0,1% quilify that Slump-Flow are about 50-65 cm and T50 are 3-15 second. Test result for compressive strength of SCC with gap graded, the optimum Vf is 0,05% with 7,02% increase in strength compared to dense graded with 0% Vf. Test result for split tensile strength of SCC with gap graded, the optimum Vf is 0,05% with 45,53% increase in strength compared to dense graded with 0% Vf. Test result for bending strength of SCC with gap graded, the optimum Vf is 0,05% with 347,28% increase in strength compared to dense graded with 0% Vf.